2013
DOI: 10.1111/psyp.12160
|View full text |Cite
|
Sign up to set email alerts
|

“Glass fairies” and “bone children”: Adolescents and young adults with anorexia nervosa show positive reactions towards extremely emaciated body pictures measured by the startle reflex paradigm

Abstract: In this study, we investigated the emotional processing of extremely emaciated body cues in adolescents and young adults with (n  =  36) and without (n =  36) anorexia nervosa (AN), introducing a new picture type, which was taken from websites that promote extreme thinness and is targeted specifically at adolescents interested in extreme thinness. A startle reflex paradigm was used for implicit reactions, while a self-assessment instrument was used for subjective responses. We found a significant group differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 47 publications
(53 reference statements)
1
21
1
Order By: Relevance
“…Bellodi et al (2013) showed lower baseline reactions of startle responses when confronting adult AN participants with blanc screens. In contrast, Reichel et al (2014) showed appetitive startle responses to positive stimuli comparable with healthy controls (HCs) in a sample of adolescents with current AN, and also appetitive responses to body pictures picked from pro-Ana websites (emaciated bodies) only in AN participants. In contrast, Reichel et al (2014) showed appetitive startle responses to positive stimuli comparable with healthy controls (HCs) in a sample of adolescents with current AN, and also appetitive responses to body pictures picked from pro-Ana websites (emaciated bodies) only in AN participants.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Bellodi et al (2013) showed lower baseline reactions of startle responses when confronting adult AN participants with blanc screens. In contrast, Reichel et al (2014) showed appetitive startle responses to positive stimuli comparable with healthy controls (HCs) in a sample of adolescents with current AN, and also appetitive responses to body pictures picked from pro-Ana websites (emaciated bodies) only in AN participants. In contrast, Reichel et al (2014) showed appetitive startle responses to positive stimuli comparable with healthy controls (HCs) in a sample of adolescents with current AN, and also appetitive responses to body pictures picked from pro-Ana websites (emaciated bodies) only in AN participants.…”
Section: Introductionmentioning
confidence: 84%
“…In anorectic patients, results regarding emotion-modulated startle are conflicting (Bellodi, Martoni, Galimberti & Cavallini, 2013;Friederich et al, 2006;Racine et al, 2016;Reichel et al, 2014), and longitudinal data are lacking. In adults with ongoing AN, Racine et al (2016) as well as Friederich et al (2006) observed a lack of startle inhibition to positive cues.…”
Section: Introductionmentioning
confidence: 99%
“…However, emerging theories argue against generalized reward deficits in AN (O’Hara et al, 2015, Wierenga et al, 2014). Indeed, recent data indicate that reward processing is enhanced in the presence of illness-compatible cues (e.g., emaciated bodies) and behaviors (e.g., physical activity) in individuals with AN (Giel et al, 2013, O’Hara et al, 2015, Reichel et al, 2014). Enhanced reward processing of certain stimuli, rather than an overall inability to experience reward, suggests that treatments should focus on shifting appetitive reactivity away from illness-compatible cues and towards stimuli associated with positive emotions in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted that patients with AN would show: 1) enhanced emotional reactivity, as indicated by a potentiated startle response, to negative and food images (compared to neutral images), and 2) difficulty suppressing emotional responses to negative and food images, as indicated by similar startle responses when receiving suppress and maintain regulation cues. Given inconsistent findings for positive images between the two previous EMSP studies in AN (Friederich et al, 2006, Reichel et al, 2014), we did not have a priori hypotheses regarding within-subject differences for positive images.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation